Development of E-Learning Physics Using Google Sites Assisted by Quizizz and PhET Simulations - Saputra, I Gede Purwana Edi (Navigation Physics : Journal of Physics Education, 2025)
The urgency of this research is driven by a range of issues encountered in the implementation of the Merdeka Curriculum, particularly concerning the development of valid, practical, effective, and efficient learning media based on E-Learning to facilitate the digitalization of schools. This is particularly relevant in the context of physics education, which demands a meticulous approach to deliver immersive learning experiences grounded in real-world phenomena. The primary objective of this study is to develop E-Learning physics using Google Sites assisted by Quizizz and PhET Simulations, that are valid, practical, and effective to enhance students' interest and engagement in learning physics. These efforts are particularly significant in the context of implementing the Merdeka Curriculum in Senior High Schools. The research methodology is Research and Development (R&D) through modification on steps of 4D Models into 3D Models (Define, Design, and Develop) with an additional quantitative descriptive analysis to gauge the extent of teacher competence in utilizing the developed products. The results show that E-Learning using Google Sites assisted by Quizizz and PhET Simulations have been validated using Gregory index, namely 0.69 for the internal consistency coefficient on the material and 0.76 for the internal consistency coefficient on the media, and proven to be effective in boosting student engagement and interest namely 82% approval rating for the media developed in the realm of physics learning , particularly within the framework of the Merdeka Curriculum.